(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
This paper examines the protagonist in T.S Eliot’s The Lovesong of J. Alfred Prufrock in relation to the existential philosophy of Jean-Paul Sartre and posits further areas for academic enquiry.